Collective care strategies for teams of the basic health unit for the elderly: Health promotion strategies for the elderly - Silva, Letícia Pacheco (2024)
Objective: To find out about the collective care strategies promoted by the minimum teams of Basic Health Units with elderly people. Methods: This is an exploratory study with a qualitative approach, carried out in five basic health units located in the municipalityof Boa Vista, capital of the state of Roraima. Twenty professionals working in the Family Health Strategy were included. The datawas produced through semi-structured interviews, from May 2021 to April 2022. The analysis was guided by Laurence Bardin’s framework and the findings were organized into two thematic frameworks. Results: Within the scope of health promotion for the elderly people, two thematic dimensions were identified, namely: group activities and health education. In the first thematic unit, collective care strategies were related to group activities for hypertensive and diabetic elderly people, physical activity groups, dance groups and collective activities on commemorative dates. The second thematic unit presented the lecture as the centrality of health education, mediated by the following themes: Chronic Non-Communicable Diseases, use of medications, and Sexually Transmitted Infections. Conclusion: Learning about the collective care strategies promoted by teams of the basic health units has brought tolight the need to rethink the practices of group activities and health education carried out in the health services. In fact, collective strategies that value health over illness and dialogical currents capable of strengthening the autonomy and the emancipation of the elderly people should be considered.